Does Short-Term Speed Endurance Soccer Training Improve Physical Performance? - I Dewa Made Aryananda Wijaya Kusuma; Nining Widyah Kusnanik; Ria Lumintuarso; Hari Setijono; Muhammad; Heryanto Nur Muhammad; Dwi Cahyo Kartiko; Gigih Siantoro; Yanyong Phanpheng (OVS LLC, 2024)
Objectives. This study is aimed at analyzing the impact of short-term Speed Endurance Soccer Training (SEST) training on the physical performance of young soccer players. Materials and methods. The true experiment method was used in this study. The study population comprised a total of 122 individuals. Furthermore, by using random sampling techniques, a sample of 30 persons was selected with an average age of 15.2 ± 0.81 years, height 168.1 ± 4.82 cm, weight 57.85 ± 11.93 kg, and BMI 20.34 ± 3.37. Physical performance instruments included the Running Based Anaerobic Sprint Test (RAST), Yo-Yo intermittent test level 1, 20-meter sprint, and standing broad jump test. The study used the paired t-test to evaluate the effect of each group and the independent samples t-test to compare the improvement in the experimental (SEST) and control groups. Statistical significance was set at p < 0.05. Results. The paired t-test showed significant differences between the pretest and post-test in the SEST group in anaerobic (p = .000, Δ% = 8.4), aerobic (p = .000, Δ% = 7.48), and speed (p = .000, Δ% = 3.39) capacities. Meanwhile, there were no considerable differences in the variables for the control group. According to the independent t-test results, a significant difference in effect between the SEST group and the CTRL group was revealed. The SEST group demonstrated marked differences in anaerobic, aerobic and speed variables with a p-value = 0.000. Conclusions. The study reveals that short-term Speed Endurance Soccer Training contributes to enhancing the physical performance of soccer players. However, caution should be exercised regarding the potential risk of hamstring injury in individuals with unprepared muscles.